An analysis of bank productivity in Indonesia: The impact of P2P lending and digital payments using the Malmquist Productivity Index - Octrina, Fajra; Eliza, Jihan; Jamilah, Almi; Dewi, Andrieta Shintia (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
This study investigates the relationship between technological adoption and banking productivity, specifically focusing on Indonesian banks over five years. Using the Malmquist Productivity Index (MPI), the study measures changes in productivity and identifies the variables that influence increases or decreases in performance. The findings reveal that P2P lending and digital payment innovations have a significant positive effect on enhancing bank productivity. Additionally, other bank-specific and macroeconomic variables were found to impact productivity levels. The results highlight the importance of continuous technological development and strategic operational improvements to sustain productivity growth. Based on these findings, it is recommended that banks intensify investments in financial technology, diversify their digital service offerings, and adapt operational models to reach broader market segments. Furthermore, regulatory bodies are encouraged to foster a competitive environment that promotes innovation while ensuring financial stability. These efforts are crucial to maintaining long-term efficiency and competitiveness in the banking sector.